2018
DOI: 10.5897/ijps2018.4775
|View full text |Cite
|
Sign up to set email alerts
|

Noise exposure levels and health implications on daily road side petty traders at some major roundabouts in Ibadan, Nigeria

Abstract: The level of noise exposure to daily road side traders at five major roundabouts in Ibadan metropolis was assessed. Noise measurements were made using a precision multi-function sound level meter. Measurements were made at three different periods of the day; morning (7:30 to 11:30 a.m.), afternoon (12:00 to 3:00 p.m.) and evening (4:00 to 5.00 p.m.) for a consecutive period of ten days. The highest mean maximum noise levels of 87.19 dBA (evening), 87.14 dBA (morning) and 87.35 dBA (afternoon) were obtained at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…Nearness of market to residential areas suggests increase in economic activities in most urban neighbourhood. Significance of market proximity further corroborates the finding of Ogunseye et al [22] as areas prone to market activities is associated with higher noise level. In promoting a conducive urban environment, strategies towards urban planning and regulations are essential in a bid to relief the residents from environmental stress.…”
Section: Difference In Spatial Pattern Of Neighbourhood Facilitiessupporting
confidence: 86%
“…Nearness of market to residential areas suggests increase in economic activities in most urban neighbourhood. Significance of market proximity further corroborates the finding of Ogunseye et al [22] as areas prone to market activities is associated with higher noise level. In promoting a conducive urban environment, strategies towards urban planning and regulations are essential in a bid to relief the residents from environmental stress.…”
Section: Difference In Spatial Pattern Of Neighbourhood Facilitiessupporting
confidence: 86%
“…Niemann and Maschke (2004) reported that road traffic noise is one of the leading causes of sleep disruption among city dwellers. Also, Ogunseye et al [2] reported that, even a relatively low level of noise causes sleep disturbance, hypertension, and hinder cognitive development among children.…”
Section: Human and Environmental Consequences Of Road Traffic Noise I...mentioning
confidence: 99%
“…The effects of traffic noise on human health and wellbeing are categorized into four depending on the period and volume which an individual is exposed to including physical, such as hearing defects; physiological, such as increased blood pressure, irregularity of heart rhythms and ulcers [2]; psychological, such as disorders, sleeplessness and going to sleep late, irritability and stress [3]; and effects on work performance, such as reduction of productivity and misunderstanding what is heard (Vibhav et al, 2018). Road traffic noise has in recent times become a global issue.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the majority of the publications primarily focus on key locations in metropolitan areas, work/marketplaces, and noise exposure and its related impact on job performance (Sirajus et al, 2014;Yesufu et al, 2012). (Ogunseye et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%